Clinical decision making ability of nursing students in a tertiary hospital. - Ho, SE; Koo, YL; Ismail S,; Hing, HL; Widad O,; Chung, HT; Nabishah M,; Liu, CY; Ho, CCK (Penerbit UKM, 2013)
Decision making in nursing is one of the most important skills nurses must apply and utilize in their nursing practice. The aim of this study was to determine the perception of clinical decision making ability among nursing students. A descriptive cross-sectional study was conducted in a tertiary hospital. A total of 54 nursing students were recruited using a modified version of Clinical Decision Making in Nursing Scale (CDMNS) adapted from Jenkins (1985). The findings showed good CDMNS score with mean and standard deviation of (124.24±12.713). The four sub-scales of CDMNS were: searching for alternative (33.24±4.821), canvassing (28.74±3.514), evaluation and re-evaluation (31.43±3.922), searching for information (30.83±4.765). Nineteen (35%) of the participants chose nursing as their first choice, whereas 35 participants (65%) did not. Thirthy seven (69%) participants were satisfied with their nursing competency, 17 (31%) were unsatisfied. There were significant differences between searching for alternatives, evaluation and re-evaluation, and nursing as their first choice (p=<0.05). There were also significant differences between searching for alternatives and satisfaction with nursing competency (p=<0.05). There was significant difference between education level and searching for alternatives and information (p=<0.05). The nursing students possessed adequate clinical decision making ability. Although most of the nursing students did not choose nursing as their first choice, they sought for alternatives and evaluated-reevaluated during their decision making process. Nursing students’ satisfaction also contributed to appropriate clinical decision making in the critical care setting.